Cartographie des milieux naturels et semi-naturels du littoral de Corse du sud - Frédéric Bioret; Françoise Gourmelon (Cybergeo, 1999)
The vegetation mapping of the South Corsica coastal area (Sartène - Porto-Vecchio) is done within the context of the International Park of Bouches de Bonifacio Project. Its main purpose is to study vegetation types and to assess the natural diversity of the site. The methodology is based on interpretation of aerial photographs at a scale of 1 : 25000 associated with field investigations and Geographical Information System technologies.